Solution-grown monocrystalline hybrid perovskite films for hole-transporter-free solar cells - Peng, W; Wang, L; Murali, B; Ho, K; Bera, A; Cho, N; Kang, C; Burlakov, V; Pan, J; Sinatra, L; Ma, C; Xu, W; et al. (Wiley, 2016)
High-quality perovskite monocrystalline films are successfully grown through cavitation-triggered asymmetric crystallization. These films enable a simple cell structure, ITO/CH3 NH3 PbBr3 /Au, with near 100% internal quantum efficiency, promising power conversion efficiencies (PCEs) >5%, and superior stability for prototype cells. Furthermore, the monocrystalline devices using a hole-transporter-free structure yield PCEs ≈6.5%, the highest among other similar-structured CH3 NH3 PbBr3 solar cells to date.